Is the proteome of bronchoalveolar lavage extracellular vesicles a marker of advanced lung cancer? - Carvalho, Ana Sofia (2020)
Funding: R.M. is supported by Fundação para a Ciência e a Tecnologia (CEEC position, 2019–2025 investigator). This article is a result of the projects (iNOVA4Health—UID/Multi/04462/2013), supported by Lisboa Portugal Regional Operational Programme (Lisboa2020), under the PORTUGAL 2020 Partnership Agreement, through the European Regional Development Fund (ERDF). This work is also funded by FEDER funds through the COMPETE 2020 Programme and National Funds through FCT—Portuguese Foundation for Science and Technology under the projects number PTDC/BTM-TEC/30087/2017 and PTDC/BTM-TEC/30088/2017. This work was supported by the Wellcome Trust/DBT India Alliance Margdarshi Fellowship (grant number IA/M/15/1/502023) awarded to A.P. B.C.-S., M.C.S.C. and C.B. are supported by the Champalimaud Foundation and the EMBO Installation Grant 3921.